2013
DOI: 10.1080/08959285.2013.836523
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Relationship Between Rater Liking and Performance Ratings

Abstract: This meta-analysis reviewed the magnitude and moderators of the relationship between rater liking and performance ratings. The results revealed substantial overlap between rater liking and performance ratings (ρ = .77). Although this relationship is often interpreted as indicative of bias, we review studies that indicate that to some extent the relationship between liking and performance ratings potentially reflects "true" differences in ratee performance. Moderator analyses indicated that the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 85 publications
3
33
0
Order By: Relevance
“…Second, others argue that performance evaluations are an indication of rater liking rather than a measure of objective performance. The more we like someone, the more likely we are to rate their performance favorably (Lefkowitz, ; Sutton, Baldwin, Wood, & Hoffman, ). The evidence from a meta‐analysis suggests that the association between rater liking and leader‐linked performance rating reported a coefficient of 0.77 (Sutton et al, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, others argue that performance evaluations are an indication of rater liking rather than a measure of objective performance. The more we like someone, the more likely we are to rate their performance favorably (Lefkowitz, ; Sutton, Baldwin, Wood, & Hoffman, ). The evidence from a meta‐analysis suggests that the association between rater liking and leader‐linked performance rating reported a coefficient of 0.77 (Sutton et al, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It is plausible that we tend to like people who are high performers. Evidence based on objective measures of performance offered support for this view (Sutton et al, ). Overall, the evidence indicated that despite the presence of subjectivity in performance evaluations, they are sufficiently merit based so as to be perceived as being fair.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the subjective and retrospective nature of this evaluation process, the assessment of an employee's professional and personal qualities are closely intertwined: Prior research has shown a strong positive relationship between supervisors' liking for employees and job performance ratings; in fact, a meta-analysis by Sutton, Baldwin, Wood, and Hoffman (2013) revealed a corrected correlation of ρ = .72 between both constructs. Based on these findings, we expect supervisor job performance ratings to reflect not only the assessment of an employee's competence as a performance-related construct, but also the interpersonal evaluation of an employee's perceived likeability.…”
Section: Introductionmentioning
confidence: 98%